Online residency training during the COVID-19 pandemic: a national survey of otolaryngology head and neck surgery program directors - Jade Chénard-Roy (BMC, 2021)
Abstract Background The COVID-19 pandemic has deeply impacted healthcare and education systems, including resident education. The impact of the pandemic on the different types of pedagogical activities, and the displacement of pedagogical activities to online modalities have not yet been quantified. We sought to evaluate the impact of the COVID-19 pandemic on formal pedagogic components of otorhinolaryngology–head and neck surgery (ORL–HNS) residency, the switch to distance learning and program director’s perceptions of the future of teaching and learning. Methods A nationwide online survey was conducted on Canadian ORL–HNS program directors. The use of standard didactic activities in-person and online, before and during the pandemic was rated with Likert scales. Perceptions of the pandemic were described with open-ended questions. Results A total of 11 of the 13 program directors contacted responded. The analysis were conducted using nonparametric statistics. There was a significant drop in overall didactic activities during the pandemic, regardless of the teaching format (3.5 ± 0.2 to 3.1 ± 0.3, p < 0.05). The most affected activities were simulation and in-house lectures. Online activities increased dramatically (0.5 ± 0.2 to 5.0 ± 0.5, p < 0.001), including attendance to lectures made by other programs (0.5 ± 0.3 to 4.0 ± 0.8, p < 0.05). Respondents stated their intention to maintain the hybrid online and in-person teaching model. Conclusions These findings suggest that hybrid online and in-person teaching is likely to persist in the post-pandemic setting. A balanced residency curriculum requires diversity in academic activities. The pandemic can have positive consequences if higher education institutions work to better support distance teaching and learning. Graphical Abstract